Design and characterization of a diamond-shaped monopole antenna - Maricar, Mohammed Ismaeel; Bahar, Ahmad; Greedy, Steve; Smartt, Chris; Phang, Sendy; Gradoni, Gabriele; Crossley, Richard; Creagh, Stephen C.; Tanner, Gregor; Thomas, David W.P. (Wiley, 2017)
We report a new planar antenna design in the shape of a diamond. The performance of the antenna design is initially obtained through simulation, then fabricated, and its performance evaluated through experiment. Experimental characterization of the diamond-shaped monopole antenna shows good agreement with simulation. In comparison with a simple monopole antenna, our diamond-shaped monopole antenna features smaller geometric footprint and displays a higher bandwidth at millimeteric wave frequencies.